Psychological treatment for people with musculoskeletal pain 2 - Pincus, Tamar (Henry Stewart Talks, 2015)
Psychological intervention trials for chronic pain, Maximizing psychological interventions, The use of cognitive-behavioural (CBT) approaches, Acceptance and commitment therapy (ACT), A comparison of CBT to ACT